Annotated list of Ensifera (Orthoptera) and further records on Caelifera (Orthoptera) of Mt Kilimanjaro, Tanzania - Hemp, Claudia (Zootaxa, 2013)
A list of the Tettigoniidae and Gryllacrididae (Orthoptera: Ensifera) of Mt Kilimanjaro is presented. A total number of 63 Ensifera was recorded for this mountain, of which 25 species belonged to Phaneropterinae, 18 to Conocephalinae, 6 to Hetrodinae and three to Pseudophyllinae. The subfamily Meconematinae contributed two species while only one species of the subfamilies Hexacentrinae, Mecopodinae and Saginae was found. Gryllacrididae contributed six species. Three spe-cies recorded in literature were not found again during the research period. 15 species are newly recorded for Mt Kiliman-jaro in this study and one species of Agraeciini newly described. Two new genera, Afroanthracites Hemp & Ingrisch n. gen. (type species: Anthracites montium Sjöstedt, 1910) and Afroagraecia Ingrisch & Hemp n. gen. (type species: Agrae-cia sansibara Redtenbacher, 1891), are erected on African Agraeciini (Conocephalinae). Anthracites kilimandjaricus Sjöstedt, 1910 is snonymized with A. montium Sjöstedt, 1910. Agraecia sansibara (Redtenbacher, 1891), Anthracites bloyeti Brongniart, 1897 and Anelytra panteli Karny are transferred to Afroagraecia. Aethiomerus stenorhinus Saussure, 1899 is synonymised with Afroagraecia sansibara (Redtenbacher, 1891). In Caelifera two Catantopinae (Acrididae) spe-cies are newly recorded for Mt Kilimanjaro and one pyrgomorphid species, Maura lurida (Fabricius, 1781), recovered again for the area.